2012
DOI: 10.1186/1472-6882-12-103
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activities of different extracts of Centella asiatica in incision and burn wound models: an experimental animal study

Abstract: BackgroundThe efficacy of Centella asiatica for incision and burn wounds are not fully understood. Here, we report the wound healing activities of sequential hexane, ethyl acetate, methanol, and water extracts of Centella asiatica in incision and partial-thickness burn wound models in rats.MethodsMale Sprague–Dawley rats weighing 250–300 g were randomly divided into incision and burn wound groups. Each group was stratified into seven subgroups: (1) untreated; (2) NSS-; (3) Tween 20®- (vehicle control); (4) hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
1
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(130 citation statements)
references
References 23 publications
4
112
1
13
Order By: Relevance
“…Data on many recent experimental studies have scientifically validated the traditional uses of the extract of Mandukaparni. These findings endorse that the plant having multiple therapeutic potentials, which were amply and vividly demonstrated by different animal models such as wound-healing model in rat, [10][11] streptozocin-induced Alzheimeir's model 12 , zebrafish Parkinson's model, 13 adriamycin-induced cardiomyopathy model, 14 nitroglycerine and bradykinin induced hyperalgesia (migraine) model, 15 radiationinduced dermatitis model, memory impairment induced by cerebral ischemia-reperfusion 16 and also having anxiolytic, 17 neuronal dendritic growth and nerve stimulating effects, 18 suppression of scars in diabetic patients, 19 and reverse mutation assay for non-toxicity, safety and nonmutagenicity of the extract, 20 protection of healthy cells against radiationinduced damages. 21 However, the botanical standards specified for evaluation of intact plant material of Centella asiatica in literature [22][23][24][25] seemed to be too scanty and not exhaustive enough to extricate the crude raw materials from the adulterants and substitutes.…”
Section: Introductionmentioning
confidence: 97%
“…Data on many recent experimental studies have scientifically validated the traditional uses of the extract of Mandukaparni. These findings endorse that the plant having multiple therapeutic potentials, which were amply and vividly demonstrated by different animal models such as wound-healing model in rat, [10][11] streptozocin-induced Alzheimeir's model 12 , zebrafish Parkinson's model, 13 adriamycin-induced cardiomyopathy model, 14 nitroglycerine and bradykinin induced hyperalgesia (migraine) model, 15 radiationinduced dermatitis model, memory impairment induced by cerebral ischemia-reperfusion 16 and also having anxiolytic, 17 neuronal dendritic growth and nerve stimulating effects, 18 suppression of scars in diabetic patients, 19 and reverse mutation assay for non-toxicity, safety and nonmutagenicity of the extract, 20 protection of healthy cells against radiationinduced damages. 21 However, the botanical standards specified for evaluation of intact plant material of Centella asiatica in literature [22][23][24][25] seemed to be too scanty and not exhaustive enough to extricate the crude raw materials from the adulterants and substitutes.…”
Section: Introductionmentioning
confidence: 97%
“…Few antimicrobial ointments such as silver sulfadiazine, mafenide, silver nitrate, povidone-iodine, mupirocin and bacitracin, are used to reduce the risk of infection in minor cuts and burns but these topical antimicrobials are not fully effective in treatment of wounds and may cause some side effects. 16 Thus there is need to develop safer drugs to combat different types of wounds. Literature available from all possible scientific sources revealed that the leaves of Hibiscus rosa-sinensis have not been evaluated for its toxicological effects and also its wound healing potential.…”
Section: Introductionmentioning
confidence: 99%
“…Yara iyileşmesini hızlandırmak ve düzenlemek amacıyla pek çok tıbbi ve geleneksel ilaç kullanımına dair halen çalışmalar yapılmakta ve yeni ürünler araştırılmaktadır. Etki mekanizmaları göz önünde bulundurulduğunda, hücre çoğalmasını, anjiogenezisi ve kollajen sentezini artırıcı ve epitelizasyonu hızlandırıcı pek çok ajan bu amaçla kullanılmakta veya araştırılmaktadır [24][25][26][27][28] . P. spinosa meyvelerinde, bir flavonoit çeşidi olan ve kardiyovasküler koruyucu, antiinflamatuvar ve antioksidan etkileri olan çeşitli antosiyaninler (siyanidin-3-rutinosit, peonidin-3-rutinozit, siyanidin-3-glikozit) bulunmaktadır 10 .…”
Section: Discussionunclassified